Luchas sociales, justicia contextual y dignidad de los pueblos - Maesschalck, M. (Marc) (Book collections on Project MUSE., 2020)
Set of works of renowned Latin American intellectuals about the current political and social situation in our region, especially after the events of Ecuador, Brazil and Chile